Awareness of Islamic banking products and services among non-muslim students in selected Northern Universities of Malaysia - Musse, Abdifatah Mohamed (2015)
Islamic financial industry has shown a positive growth that attracts many investors and clients worldwide. Malaysia, one of the pioneer members of this emerging industry is also experiencing notable development in operating more than seventeen Islamic banking institutions. However, non-Muslim clients experienced difficulties when it comes to understanding of overall system, principles, features and sophisticated Arabic terms that Islamic banks use. The purpose of this research is to examine the level of awareness, understanding and perceptions of non-Muslims in selected northern universities of Malaysia towards Islamic banking products and services. In addition, this study also aims to investigate if there are any demographic factors influence the awareness, understanding and perceptions of Islamic Banking products and services among non- Muslim students in selected universities. The result showed that the vast majority of respondents generally aware of Islamic banking products and services. Nevertheless, the result also indicated that non-Muslim students do not have enough knowledge and understanding towards Arabic terms that Islamic Banks use in their products and services. The study found that there is significant relationship between understanding and awareness. Furthermore, the result showed that there is no significant relationship between perception and awareness. Moreover, the study found that demographic factors such as age, religion, and level of education show significant differences among respondents, while gender show no significant difference among the respondents. This study contributes to the available literature in Islamic banking Industry in general while imparts in managerial aspects through its recommendations. It suggests that Islamic banking managers should take all necessary steps to adopt marketing policies and other endeavours in order to make sure that all clients of Islamic banks should have a maximum awareness, understanding and positive perception towards the products and services of Islamic banking